Research on the Impact of Globalization on Education in Indonesia - Danga, Agnesis Yaku (International Research Journal of Management, IT & Social Sciences, 2015)
The aims of this study are 1) For Readers; This paper proposed to discuss the impact of globalization on the world of education and increase know ledge on globalization the readers of the dominant Â of the students can be used to move towards a broader knowledge so that future human resources achieved superior. 2) For Society; It is hoped that people can understand the meaning of the negative impacts of globalization research the impact that can be minimized and positive activity to education which is getting better.